The unspoken presentation of the uncommon : superior vena cava syndrome - Loo, Susan Pooi San; Siti Nidzwani MM (Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Superior vena cava syndrome is a medical emergency. The morbidity and mortality of superior vena cava syndrome can be decreased by early recognition, early establishment of primary cause, early supportive and definitive treatment. We illustrate a case of 53-year-old male with underlying advanced Parkinsonism and ischemic stroke who presented with superior vena cava syndrome over 4 days period. Diagnostic challenge in this patient lies in the fact that patient had aphasia and his daily living activity was dependent. Most of the information was based on caretaker’s observations. A strong clinical suspicion based on clinical history is crucial for early diagnosis and treatment of superior vena cava syndrome.